Application of the Teams-Games Tournament Learning Model, Problem-Based Learning, and Direct Instruction in Mathematics Learning about Statistics - Andreas Pandeirot; Vivian E. Regar; Ontang Manurung (Departement of Mathematics Education, 2023)
This study aims to determine whether there are differences in the learning outcomes of students who are taught statistics using the DI, TGT, or PBL models. Class VIII A is taught using the TGT cooperative learning model, Class VIII B is taught using the PBL cooperative learning model, and Class VIII C is taught using the DI cooperative learning model. One-way analysis of variance (One-Way Analysis of Variance) is the research design used. After the treatment, the results of the post-test measurement of student learning outcomes were used to compile data. The research method used is quasi-experimental. Based on the ANOVA hypothesis test with a significance level of 0.05, Fcount = 4.3068056 > Ftable = 3.150, indicating that H0 is rejected and H1 is accepted. Therefore, the average learning outcomes of students taught by the DI model, suitable TGT type, and PBL differ. So that additional tests can be carried out using the BNT test and the results obtained. The average learning outcomes of students taught using the DI model were significantly lower than those taught using the TGT model (mean = 83.13636). The average learning outcomes of students taught by the DI model (mean = 73.19047) are different from those of students taught by the PBL learning model (mean = 82.1429), while the average learning outcomes of students taught by cooperative learning type TGT and PBL are identical.